2020
DOI: 10.1093/eurheartj/ehaa598
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging-guided repair after acute myocardial infarction by targeting the chemokine receptor CXCR4

Abstract: Aims  Balance between inflammatory and reparative leucocytes allows optimal healing after myocardial infarction (MI). Interindividual heterogeneity evokes variable functional outcome complicating targeted therapy. We aimed to characterize infarct chemokine CXC-motif receptor 4 (CXCR4) expression using positron emission tomography (PET) and establish its relationship to cardiac outcome. We tested whether image-guided early CXCR4 directed therapy attenuates chronic dysfunction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 24 publications
4
78
2
Order By: Relevance
“…However, besides the relatively small patient number, this study was limited by its varying imaging and follow-up time points as well as lacking data on CXCR4/CXCL12 levels to determine endpoints of molecular inflammation. Moreover, the findings of this study are in contradiction to two recently published studies suggesting beneficial effects of CXCR4 blockade in mice with MI [30,31]. The more recent one of these studies reported that the timing of CXCR4 blockade is important and that CXCR4-directed PET imaging can serve as a tool for therapeutic guidance to determine the right timing of treatment.…”
Section: Chemokine Receptorscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, besides the relatively small patient number, this study was limited by its varying imaging and follow-up time points as well as lacking data on CXCR4/CXCL12 levels to determine endpoints of molecular inflammation. Moreover, the findings of this study are in contradiction to two recently published studies suggesting beneficial effects of CXCR4 blockade in mice with MI [30,31]. The more recent one of these studies reported that the timing of CXCR4 blockade is important and that CXCR4-directed PET imaging can serve as a tool for therapeutic guidance to determine the right timing of treatment.…”
Section: Chemokine Receptorscontrasting
confidence: 99%
“…The more recent one of these studies reported that the timing of CXCR4 blockade is important and that CXCR4-directed PET imaging can serve as a tool for therapeutic guidance to determine the right timing of treatment. Hess and colleagues further showed a correlation of CXCR4 expression in acute MI patients with cardiac outcome and inflammation parameters suggesting prognostic value of 68 Ga-pentixafor PET [31].…”
Section: Chemokine Receptorsmentioning
confidence: 97%
See 1 more Smart Citation
“…The intensity of the PET imaging signal at 3 days after injury predicted the severity of ventricle remodeling and contractile dysfunction 6 weeks later, independent of the infarct size. Moreover, mice with prolonged upregulation of CXCR4 over 3 days after ischemic injury had a higher incidence of acute ventricle rupture [ 44 ••]. Patients after acute infarction exhibit variable CXCR4 signal [ 45 , 46 ], but the imaging signal obtained 4−6 days after reperfused myocardial infarction also correlates with contractile function 6−9 months later [ 44 ••].…”
Section: Imaging Inflammationmentioning
confidence: 99%
“…Regional inflammation could be directly treated by antiinflammatory agents, gene therapy to promote endogenous repair, or immunomodulatory therapy to target adverse remodeling processes. 13,14 Such approaches could overcome the hazards of systemic immunomodulation. Alternatively, prior studies have reported alignment of nuclear cardiac images to catheter-based measures of electrophysiology, where the site of inducibility of ventricular arrhythmia corresponded to lower retention of norepinephrine analogues.…”
mentioning
confidence: 99%